Biochemistry - Hames, David; Hooper, Nigel ([S.l.] : Taylor & Francis, 2005)
A major update of the highly popular second edition, with changes in the content and organisation that reflect advances in the subject. As with the first two editions, the third edition of Instant Notes in Biochemistry provides the essential facts of biochemistry with detailed explanations and clear illustrations. It also includes new and expanded topics such as cytoskeleton, molecular motors, bioimaging, biomembranes, cell signaling, protein structure and enzymes regulation.
Keywords: biochemistry